Analyzing Online Shopping Behavior from the_x000D_ Perspective of Youtube: Do Vlog Content and Vlogger_x000D_ Characteristics Matter - EKİZLER, HÜSEYİN (My University, 2021)
Video blogs (Vlogs) and video bloggers (Vloggers) have gained importance in marketing with theirentertaining and educational content as they are attracting huge numbers of viewers and are thereforeshaping many consumers’ attitudes and purchase decisions. Research on vlogs concentrated oncontent characteristics, vlogger characteristics and general vlog features. However, this stream ofresearch is fragmented, mostly ignores vlog audience motivations and lacks empirical investigationsthat parsimoniously study influence of certain vlog and vlogger characteristics on consumers’ onlinepurchase decisions. The purpose of this study is to explore the impact of vlog content value in terms ofinformativeness and entertainment and vlogger personal characteristics such as authoritative andengagement knowledge on consumers’ information satisfaction and further on their intention to shoponline. With this aim, data were gathered via an online survey from 627 purposively sampledrespondents and a theoretical structural equation model was tested. Vlog content’s informative andentertaining value and authoritative knowledge of the vlogger were found to be important factorsexplaining information satisfaction, whereas the effect of engagement knowledge on informationsatisfaction was insignificant. Furthermore, strong impact of information satisfaction on intention toshop online was determined. Managerial and theoretical implications are discussed in the paper.

Video blogları (Vlog'lar) ve video blog içerik üreticileri (Vlogger’lar), eğlenceli ve eğitici içerikleriyle_x000D_ çok sayıda izleyiciyi cezbettikleri için tüketicinin tutumlarını ve satın alma kararlarını_x000D_ şekillendirmelerinden dolayı pazarlamada önem kazanmıştır. Vloglar üzerine yapılan çalışmalar içerik_x000D_ özellikleri, vlogger özellikleri ve genel vlog özellikleri üzerinde yoğunlaşmıştır. Ancak bu çalışmaların_x000D_ birbirinden kopuk olduğu ve vlog izleyen kitlenin motivasyonlarını göz ardı ettiği ve belirli vlog içeik_x000D_ ve vlogger özelliklerinin tüketicilerin çevrimiçi satın alma kararlarına etkisini ayrıntılı bir şekilde_x000D_ inceleyen empirik çalışmalardan yoksun olduğu görülmektedir. Bu çalışmanın amacı, bilgi ve eğlence_x000D_ açısından vlog içerik değerinin ve yetkili bilgisi ve katılım bilgisi gibi vlogger kişisel özelliklerinin_x000D_ tüketicilerin bilgi memnuniyeti ve ayrıca çevrimiçi alışveriş yapma niyetleri üzerindeki etkisini_x000D_ araştırmaktır. Bu amaçla, veriler kasıtlı olarak örneklenmiş 627 katılımcıdan çevrimiçi anket yoluyla_x000D_ toplanmış ve teorik bir yapısal eşitlik modeli test edilmiştir. Vlog içeriğinin bilgilendirici ve eğlenceli_x000D_ değeri ve vloggerın yetkili bilgisi, bilgi memnuniyetini açıklayan önemli faktörler olarak bulunurken,_x000D_ etkileşim bilgisinin bilgi memnuniyeti üzerindeki etkisi anlamlı bulunmamıştır. Ayrıca bilgi_x000D_ memnuniyetinin online alışveriş yapma niyeti üzerindeki güçlü etkisi tespit edilmiştir. Yönetsel ve_x000D_ teorik çıkarımlar makalede tartışılmaktadır.
Online Alışveriş Davranışının Youtube Perspektifinden Analizi: Vlog İçeriği ve Vlogger Özellikleri Etkili Mi?